AI COURTROOM: AN AI-POWERED LEGAL LEARNING & TRIAL PREPBOT (Lex localis - Journal of Local Self-Government, 2025)
An AI-driven Courtroom simulation for Indian Law marks a transformational step in the realm of legal education. Alongside theoretical knowledge, practical exposure of the same teachings propels students to learn better, in a more engaged manner. This research combines the use of Natural Language Processing (NLP) along with Large Language Models (LLM) to ensure that users can communicate with the system via the use of textual inputs. Users, who can play the role of an attorney, receive relevant, real-time responses from the system which comprises of an opposing AI counsel and a simulated AI Judge. To add an element of realism to the userexperience, this application also produces synthetic cases that are derived from real life scenarios. These efforts make sure that students, irrespective of their financial or social backgrounds can utilize this application to get hands-on experience in a courtroom setting, hence filling the gap between classroom learning and real-world exposure, while enhancing the accessibility of the same.